2015
DOI: 10.2139/ssrn.2678794
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Violence and Housing Insecurity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…This is true regardless of whether the shocks are on average harmful (homelessness is scarring) or helpful (homelessness aids recovery). Diette and Ribar (2018) look at the compound outcome of homelessness (approximately cultural) and violence. Both men and women in the Journeys Home sample experience violence at high rates, and both violence and housing instability in one period lead to violence and housing instability six months later, for both men and women.…”
Section: Journeys Homementioning
confidence: 99%
“…This is true regardless of whether the shocks are on average harmful (homelessness is scarring) or helpful (homelessness aids recovery). Diette and Ribar (2018) look at the compound outcome of homelessness (approximately cultural) and violence. Both men and women in the Journeys Home sample experience violence at high rates, and both violence and housing instability in one period lead to violence and housing instability six months later, for both men and women.…”
Section: Journeys Homementioning
confidence: 99%
“…For example, Lee & Schreck (2005) find that different risky lifestyle behaviors (such as sleeping outdoors or panhandling), increase ones risk of violent and property victimization, along with other more distal and demographic factors in a cross-sectional survey. Diette & Ribar (2018) examine victimization in a longitudinal panel design, and find that housing insecurity increases future risk of violence, independent of prior risks of violence. The findings appear similar for offending as well, with Crawford, Whitbeck, & Hoyt (2009) finding that self-reported measures of violent offending among a sample of juveniles were more likely among homeless youth that participated in selling drugs or were in a gang, as was a history of caretaker abuse.…”
Section: Homelessness and Crimementioning
confidence: 99%
“…Homelessness is not a monolithic category. Most individuals are not chronically homeless, but experience more brief, intermediate spells (Diette & Ribar, 2018). The needs of the intermittently homeless may be easier to address than the chronic homeless (Listwan et al, 2018), but the ability of the state to intervene on their behalf is much more limited.…”
Section: Homelessness and Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Adequate housing is also related to the psychological and social well-being of residents [ 20 ]. While most of the research on housing insecurity focuses on physical health outcomes, mental health or the psychological benefits of adequate housing, there is some evidence that housing insecurity is associated with crime [ 17 , 21 , 22 ]. For example, in a qualitative study of women victims, housing instability along with food insecurity were identified as key contributors to intimate partner violence [ 17 ].…”
Section: Introductionmentioning
confidence: 99%